DESIGNING LAGUNDRI BEACHFRONT ROSERT HOTEL WITH NEO-VERNACULAR ARCHITECTURAL APPROACH - Humendru, Jonathan A.; Ginting , Nurlisa (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
In general, not all tourist areas provide facilities that support the regional tourism sector well enough. Some only provide makeshift facilities so that the level of comfort and satisfaction for visitors to the area is not too high. For example in the Lagundri area, tourism in this area has good prospects, but the level of optimisation of the facilities provided is far from sufficient. So it is necessary to increase facilities that are able to support the development of the tourism sector. So designing a resort hotel in this area is one solution that can be achieved. The purpose of this paper is to find out how to design the right resort hotel to support the tourism potential in the Lagundri area. The method used in this research is a qualitative method, namely by using problem analysis through literature studies in the form of journals, articles and other forms of literature that help in the design stage. As the right solution, of course, the resort must be built by paying attention to aspects of design, spatial planning, as well as the use of materials and locality or local culture. Therefore, it is necessary to design a resort with a neo-vernacular architectural approach as a solution to support tourism activities that show the existing local identity so that this tourist area can be maximised. So that this development can help the local community and government.